Twistors and Bi-Hermitian Surfaces of Non-Kähler Type - Fujiki, A.; Pontecorvo, M. (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
The aim of this work is to give a twistor presentation of recent results about bi-Hermitian metrics on compact complex surfaces with odd first Betti number.